Historic Corporate Social Responsibility - Schrempf-Stirling, Judith; Palazzo, Guido; Phillips, Robert A. (Academy of Management Review, 2016)
Corporations are increasingly held responsible for activities up and down their value chains but outside their traditional corporate boundaries. Recently, a similar wave of criticism has arisen about corporate activities of the past, overseen by prior generations of managers. Yet there is little or no scholarly theorizing about the ways contemporary managers engage with these critiques or how this corporate engagement with the past affects the legitimacy of current business. Extending theorizing about political corporate social responsibility and organizational legitimacy, we address this omission by asking the following: (1) What is the theoretical basis for holding a corporation responsible for decisions made by prior generations of managers? (2) What is the process by which such claims are raised and contested? (3) What are the relevant features that render a charge of historical harm-doing more or less legitimate in the current context? (4) How will a corporation’s response to such charges affect the intensity of the future narrative contests and the corporation’s own legitimacy?